The Effect of Cyberbullying Face Treatening Acts and Face Management on the Development of Relationships Between Perpetrators and Victims of Cyberbullying Class I Students: Pengaruh Cyberbullyng Face Treatening Acts dan Face Manajemen terhadap Pengembangan Hubungan antara Pelaku dan Korban Cyberbullying Siswa Kelas IX - Mahfud, Muhammad; Abadi, Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2023)
The development of information technology and social media has an impact on changes in human behavior in communicating. Unsupervised communication in a social environment can have a variety of deviant effects, for example, what we often hear lately with the term cyberbullying. Many students or young generations currently use social media to communicate with each other with their friends. Not a few cases that have happened to the younger generations about cyber bullying. The purpose of this study is to analyze and explain the face treatment act and face management as well as the development of inter-group and cyberbullying victims on social media. The method used is descriptive method, using a quantitative approach. The types and sources of data obtained are primary and secondary data sources. While the data collection technique used is a questionnaire to test the validity of the data using validity, reliability, and hypotheses. The results of this study indicate that there is a positive and significant relationship between the behavior of cyberbullying perpetrators and the behavior of victims of cyber bullying with a significant value which is the more reactive the behavior of cyberbullying perpetrators is, the more reactive the behavior of cyberbullying victims will be. Therefore, the government needs to hold seminar programs for parents and so that they know how to deal with cyberbullying problems faced by their children.